Incidence and nature of complications post primary repair of Obstetric Anal Sphincter Injury (OASI): Retrospective chart review - Paulsen, Carrie (Department of Obstetrics and Gynaecology, 2020)
Background. A multitude of data exists regarding global incidence of OASI as well as its contributing factors and complications. Little to no data exists regarding the incidence of OASI or its complications and the nature of these complications within South Africa. Objective. To describe the rate and nature of complications of OASI that occur within 6 weeks following primary repair of an OASI, followed up at the GSH perineal clinic. Secondarily, to investigate the incidence of OASI and follow up rate post primary repair Methods. This was a retrospective chart review. Participants were identified from theatre record books between January 2014 and December 2015. The charts of those that attended the perineal clinic follow up were reviewed and complications and possible associated risk factors were identified from the clinical notes. Primary aims were to identify the incidence and nature of complications seen in this population as well as possible related risk factors. The secondary aims were to determine the incidence of OASI and follow up rate for complication following primary OASI repair. Results. The mean age of participants was 25.85 years with a mean body mass index of 25.15kg/m2 . The mean birthweight seen was 3382.05 grams. Constipation (10.87%), pain with defaecation (11.96%) and anal incontinence (10.87%) were the most frequently reported complications. Wound infection was found on examination in 3.26% of participants and wound dehiscence was seen in 6.67%. Incidence of OASI in this study group was 8.64 per 1000 vaginal deliveries. The follow up rate of these participants was 26.20%. A total of 374 OASI were repaired within this region during the study period. Only 97 of these attended follow up, for which 93 folders were available to be included in analysis Conclusion. The Incidence of OASI in this Western Cape region is within the range seen worldwide but the proportion of complications seem to be less than global data suggests despite adverse conditions, theatre delays and the fact that repairs were mostly performed by specialists in training. It was not possible to identify any relationship with possible associated factors. There is a very poor follow up rate within this community which needs to be explored and systems need to be put in place to ensure all participants are given the opportunity of follow up.